Study on Playing Games in Computers without Physical Interaction Using Electroencephalography for Differently Abled - Sreedevi, B.; Rayavel, P. (Advanced Aspects of Engineering Research Vol. 5, 2021)
Mind Controlled Gaming for the Differently Abled seeks to give people with special needs access to the world of gaming entertainment. The project is designed in such a way that it allows people to play games without having to interact physically with the game, such as by typing on a keyboard. The project makes use of the human brain's capacity to promote this type of physical activity without resorting to gaming. It works on the basis of electroencephalography, an electrophysiological method for detecting brain electrical activity. We use noninvasive electrode placement on the scalp. EEG measures voltage variations caused by ionic current in the brain's neurons, which are then mapped to specific tasks that can be done in the games.